The parables of Jesus the Galilean : stories of a social prophet - Van Eck, Ernest (Matrix--the Bible in Mediterranean context., 2016)
Who do we meet in the stories Jesus told? In The Parables of Jesus the Galilean: Stories of a Social Prophet, a selection of the parables of Jesus is read using a social-scientific approach. The interest of the author is not the parables in their literary contexts, but rather the parables as Jesus told them in a first-century Jewish Galilean sociopolitical, religious, and economic setting. Therefore, this volume is part of the material turn in parable research and offers a reading of the parables that pays special attention to Mediterranean anthropology by stressing key first-century Mediterra.